Predicting compressive strength of concrete using impact modulus of toughness. (June 2021) - Saleem, Muhammad Azhar; Saleem, Muhammad Mazhar; Ahmad, Zeeshan; Hayat, Sikandar
Abstract: Nondestructive testing (NDT) has wide spread application in construction industry. Existing structures are tested to establish their in-place strength when any alteration in the structural components or usage of the structure is required. Sometimes, NDT is also needed to assess the condition of a structure hit by natural disasters like an earthquake or hurricane. Core test is a one such popular NDT method which is used to determine the concrete strength. Common size of core ranges from 75 mm to 100 mm. Extracting the core, however, becomes challenging when steel bars are very closely spaced. Such situation happens frequently in columns and walls. This research work proposes to extract 25 mm∅ cylindrical specimens from the concrete and test them for impact modulus of toughness (MoT) to indirectly predict the compressive strength. Experimental work was carried out in three phases. Phase 1 consisted of testing mortar specimens whereas phase 2 and 3 comprised of testing concrete specimens. Based on the results, a relationship between compressive strength and impact-MoT has been proposed, which may be used to predict the compressive strength if impact-MoT is known. Statistical analysis of result also suggests that a strong relationship exists between the compressive strength and impact-MoT.